2006
DOI: 10.1111/j.1468-1331.2006.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

The corticobasal syndrome triggered by central pontine myelinolysis

Abstract: Single case reports have described movement disorders including parkinsonism, dystonia and chorea, but not corticobasal syndrome as a consequence of central pontine and extrapontine myelinolysis. We report a case of a 61-year-old woman who developed progressive asymmetric parkinsonism with ideomotor apraxia and cortical sensory deficits following central pontine myelinolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…This leads to loss of inhibitory striatonigral feedback regulation 16 . Shamim et al reported a case of corticobasal syndrome following CPM in an elderly lady who developed progressive asymmetric parkinsonism with ideomotor apraxia and cortical sensory deficits 17 . One of our patients (Patient‐8) had corticobasal syndrome like presentation but without cortical signs and FDG = PET was not consistent with corticobasal syndrome.…”
Section: Discussionmentioning
confidence: 74%
“…This leads to loss of inhibitory striatonigral feedback regulation 16 . Shamim et al reported a case of corticobasal syndrome following CPM in an elderly lady who developed progressive asymmetric parkinsonism with ideomotor apraxia and cortical sensory deficits 17 . One of our patients (Patient‐8) had corticobasal syndrome like presentation but without cortical signs and FDG = PET was not consistent with corticobasal syndrome.…”
Section: Discussionmentioning
confidence: 74%
“…In other patients, however, cerebral lesions compatible with myelinolysis were only evident in the pons, and they still had movement disorders, with parkinsonism as the most common manifestation. Symptoms usually manifest acutely, but also late presentations with a chronic and progressive course have been described, both for dystonia and parkinsonism [5,7]. We were not able to precisely date the myelinolysis of the pons in our patient, as the only symptom he manifested was an intense daily headache for many years before he underwent a first MRI, but we can affirm that the onset of parkinsonism was surely delayed with respect to the pontine lesion compatible with myelinolysis.…”
mentioning
confidence: 58%
“…Moreover, the lesions in deep nuclei remained stable over time (Figure 2). ODS and idiopathic Parkinson's disease (PD) could be independently present in our patient, but it has been postulated that pontine myelinolysis may act as a trigger of a neurodegenerative process [7]; this may be the case for our patient. Of note, the patient had no other non-motor symptoms typical of PD, i.e., sleep disturbances and sensory disturbances, such as reduced olfactory perception, a typical and early symptom of this disease [8,9].…”
mentioning
confidence: 71%